2001
DOI: 10.1161/hq1001.097781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Statins on Bone Mineral Density and Bone Histomorphometry in Rodents

Abstract: Abstract-Statins have been postulated to affect bone metabolism. We investigated the effects of different doses of simvastatin (1,5,10, and 20 mg · kg Ϫ1 · d Ϫ1 ), atorvastatin (2.5 mg · kg Ϫ1 · d Ϫ1 ), and pravastatin (10 mg · kg Ϫ1 · d Ϫ1 ) administered orally for 12 weeks to intact female Sprague-Dawley rats and the effect of 20 mg · kg Ϫ1 · d Ϫ1 simvastatin in sham-operated and ovariectomized rats on femoral bone mineral density (BMD) and quantitative bone histomorphometry (QBH) and compared them with cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 34 publications
3
95
3
1
Order By: Relevance
“…Likewise, longitudinal studies in humans have reported an inhibitory effect of the statins on the osteoblastic activity 20,43) . However, most of these data were obtained over shorter treatment periods than the 3 -year treatment period employed in our study, and were obtained using different statins at different dosages, which has been reported to have differential effects on the activity of bone cells in rats 44) . Although the number of patients in our study is limited, the findings of no significant changes of the serum OC or u -DPD in the fluvastatin -treated group as compared with that in the control group during the study period could suggest an imbalance between bone formation and resorption.…”
Section: Discussionmentioning
confidence: 90%
“…Likewise, longitudinal studies in humans have reported an inhibitory effect of the statins on the osteoblastic activity 20,43) . However, most of these data were obtained over shorter treatment periods than the 3 -year treatment period employed in our study, and were obtained using different statins at different dosages, which has been reported to have differential effects on the activity of bone cells in rats 44) . Although the number of patients in our study is limited, the findings of no significant changes of the serum OC or u -DPD in the fluvastatin -treated group as compared with that in the control group during the study period could suggest an imbalance between bone formation and resorption.…”
Section: Discussionmentioning
confidence: 90%
“…An increased risk of cardiovascular death for each 1 SD decrease in bone mass has been demonstrated [106], and vascular calcification is associated with a higher relative risk of vertebral fractures [107]. It is also noteworthy that a class of cholesterol-lowering drugs known as statins has been shown to induce bone formation in cell cultures and rodents [108][109][110], although the findings in humans are inconclusive [111][112]. Aerobic exercise has favorable effects on lipid profiles [113][114][115] and endothelial function [116][117][118].…”
Section: Exercise To Improve and Maintain Bone Health Poststrokementioning
confidence: 99%
“…In vivo, the effects are even more contradictory. Although there are studies which agree with the original findings of Mundy et al (Garrett et al 2001, Oxlund et al 2001, Sugiyama and Kawai 2001, Garrett and Mundy 2002, Kajinami et al 2003, Staal et al 2003, Wong and Rabie 2003, Kawane et al 2004, Stein et al 2005, Gutierrez et al 2006, Garrett et al 2007), some very conscientiously designed studies have not been able to demonstrate any such effects (Maritz et al 2001, von Stechow et al 2003, Yao et al 2006.…”
Section: Statinsmentioning
confidence: 67%